2009
DOI: 10.1177/147323000903700219
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Serum Carcinoembryonic Antigen (CEA), Cancer Antigen 125 (CA125), Carbohydrate Antigen 19-9 (CA19-9), Carbohydrate Antigen 15-3 (CA15-3), α-Fetoprotein (AFP) and Human Chorionic Gonadotropin (hCG) Levels in Determining the Malignancy of Solitary Pulmonary Nodules

Abstract: We investigated the utility of the tumour markers carcinoembryonic antigen (CEA), cancer antigen 125 (CA125), carbohydrate antigen 19-9 (CA19-9), carbohydrate antigen 15-3 (CA15-3), α-fetoprotein (AFP) and human chorionic gonadotropin (hCG) for the differential diagnosis of benign and malignant solitary pulmonary nodules in 42 hospitalized patients. Routine medical history and physical examination of each patient was performed and each patient also had a chest X-ray and a thoracic computed tomography scan. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…In addition, the diagnostic performance of the combination panel of miR-148/152 family (AUC, 0.789) was significantly higher than that of CEA (AUC, 0.506). As a widely used diagnostic biomarker for NSCLC patients, CEA is found to confer good specificity but relatively poor sensitivity for the diagnosis of NSCLC [ 13 ]. In addition to having a higher diagnostic value, the sensitivity of the miR-148/152 family panel was also higher (72.2%) than that of CEA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the diagnostic performance of the combination panel of miR-148/152 family (AUC, 0.789) was significantly higher than that of CEA (AUC, 0.506). As a widely used diagnostic biomarker for NSCLC patients, CEA is found to confer good specificity but relatively poor sensitivity for the diagnosis of NSCLC [ 13 ]. In addition to having a higher diagnostic value, the sensitivity of the miR-148/152 family panel was also higher (72.2%) than that of CEA.…”
Section: Discussionmentioning
confidence: 99%
“…In the Swensen model, factors such as age, smoking history, history of other cancers, diameter, spiculation, and location of the nodules have important significance in judging between benign and malignant nodules [15]. We found that age, smoking history, emphysema, diameter, spiculation, and vascular sign have statistical significance in differentiating benign and malignant nodules.…”
Section: Discussionmentioning
confidence: 97%
“…The diagnosis of malignant SPN remains a clinical challenge at present. Although numerous studies have demonstrated that multiple serum biomarkers, including CEA, cytokeratin 19 fragment and CA125, are elevated in malignant SPN, the diagnostic performance of these biomarkers alone is not sufficient for clinical application. We describe, for the first time, measurement of serum MIC‐1 expression from malignant SPN patients, and benign SPN patients including tuberculosis, pneumonia, and patients with hamartoma.…”
Section: Discussionmentioning
confidence: 99%